Ignatius of Antioch: a martyr bishop and the origin of episcopacy - Brent, Allen (T & T Clark theology, 2007)
Ignatius of Antioch (died c. 115) is one of the Apostolic Fathers of the Christian Church. In his letters to other churches he re-interpreted church order, the Eucharist and martyrdom against the backcloth of the Second Sophistic in Asia minor by using the cultural material of a pagan society. He so formed  the idea and theology of the office of a bishop in the Christian church.  This book is an account of the circumstances and the cultural context in which Ignatius constructed what became the historic church order of Christ